Reliability of Dubbed Technical Systems with Built-In Control Device - V. A. Anishchenko; E. A. Myslo; A. N. Ivanova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
The paper substantiates a selection of passive or active system for dubbing technical systems in accordance with characteristics pertaining to probability of no-failure operation and mean–time-between failures with due account of non-reliability of a built-in control device and systems complexity.